Enhancing transboundary flood forecasting for early warnings in the Gash River Basin - Amarnath, Giriraj; Alahacoon, Niranga; Gismalla, Y.; Mohammed, Y.; Sharma, Bharat R.; Smakhtin, Vladimir (2025)
Historically, flooding is the most common environmental hazard worldwide, and also one of the most threatening to communities. Hydrological modeling of large river catchments has become a challenging task for water resources engineers due to the complexity of collecting and handling both spatial and nonspatial data, such as rainfall, gauge-discharge data, and topographic and hydraulic parameters. The Gash is a transboundary river which originates from the Eritrean Highlands and Ethiopian Plateau and ends up in Sudan. It is unique in its discharge flows with torrential rain between Jul. and Oct. while being dry for the rest of the year. Despite this characteristic, the river is the main source of water for domestic and agricultural use in Kassala City, Sudan.